(3fXe eNJUQ GdSfhSi aj GdefWbs - (3YHO GdSdGe GdMSfj GdbGOQis; (3GdSfhSj , eMeO Hf jhSa Hf YeQ Hf TYjH GdMSfj, CHh YHO Gddg,J (B895 (3g` s
(3ChdgG (B:s
(3fXe eNJUQ jMhi ajg GdefWb eNJUQ GdTjN GdSfhSi s
(3BNQgG (B:s
(3Ke GdUdGI hGdSdGe Ydi GdfHi (B,(3hBdg GdcQGe s
(3Hg fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs